A method for preparing agar with high water retention and high gel strength

By using STPP or SPP esterified agar powder under alkaline conditions, the problem of reduced gel strength and narrow application range after agar modification is solved, and modified agar with high water retention and high gel strength is achieved, which simplifies the process and Reduced costs.

CN116375906BActive Publication Date: 2024-12-17JIMEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310339284.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2024-12-17
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

The existing agar modification methods lead to reduced gel strength, narrow application range, and cumbersome process, long time-consuming, and the need for catalysts and dangerous reagents.

Method used

The agar is modified by using sodium tripolyphosphate (STPP) or sodium pyrophosphate (SPP) as the esterifying agent. The agar powder is added to STPP or SPP aqueous solution and stirred, filtered, washed and baked under alkaline conditions. Dry, and obtain modified agar with high water retention and high gel strength.

Benefits of technology

It has achieved the improvement of the gel strength and water retention of agar, simplified the process flow, reduced costs, avoided the use of catalysts and dangerous reagents, and expanded the application range of agar in food.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116375906B_ABST
    Figure CN116375906B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing agar with high water retention and high gel strength. First, agar powder is added to an STPP or SPP aqueous solution and reacted, and stirring is performed while adding. During the addition and reaction process, the temperature is kept at 30-60°C and the pH is alkaline; then the reactant is filtered, repeatedly washed with water for several times, and then crushed and sieved after drying to obtain a modified agar with high water retention and high gel strength. The prepared modified agar can improve the gel strength while improving the water retention. The method is simple in process and cost-saving. The original agar properties are improved, the application range of agar in food is increased, and the utilization value of agar is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of agar deep processing, and in particular to a method for preparing agar with high water retention and high gel strength. Background Art

[0002] Agar is a natural water-soluble high molecular weight polysaccharide extracted from seaweed. It is the first alginic colloid used in the human food industry and one of the most widely used alginic colloids in the world. Due to the unique gel properties of agar, it is widely used as a gelling agent, stabilizer and cryoprotectant in processed foods, cosmetics and medicines. However, due to the single agar powder product on the market and the few derivative products, some agars show severe dehydration, poor elasticity, poor hardness and other shortcomings in application, and their commercial value in application is also very limited. Therefore, it is of great significance to modify agar by derivatization and then change its processing characteristics in application to broaden the application of agar. The gelling temperature, dissolution temperature, apparent viscosity and gel strength of agar acetate prepared by Xia Kai et al. have all decreased, among which the gel strength has increased from 1930g / cm 2 Reduced to 530g / cm 2 (DS=0.365). The gelling temperature, melting temperature and gel strength of hydroxypropyl agar prepared by Zhang Xiaodong et al. decreased, and the gel strength decreased from 1070 g / cm2 to 200 g / cm2 (DS=0.557). Cao Mingzhao et al. prepared carboxymethyl agar. The introduction of carboxyl groups into agar molecules hindered the aggregation of the double helix structure of agar, resulting in a decrease in gel strength from 1920 g / cm 2 The minimum is reduced to 20g / cm2 (DS=0.495). Zhang Xiaodong et al. prepared hydroxymethyl agar by propylene oxide propylation, and the hygroscopicity of agar was enhanced after modification. However, the above method has the disadvantages of complicated process, long time consumption, large amount of raw materials consumption, and the need for catalysts and some dangerous reagents. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing agar with high water retention and high gel strength in view of the problems that the gel strength after modification is reduced and the application scope in the food industry is narrow in the existing agar modification method. The method uses sodium tripolyphosphate (STPP) or sodium pyrophosphate (SPP) as an esterifying agent to modify agar. The prepared modified agar can improve the gel strength while improving the water retention. The method is simple in process and cost-saving. The original agar properties are improved, the application scope of agar in food is increased, and the utilization value of agar is further improved.

[0004] To achieve the above object, the present invention provides a method for preparing agar with high water retention and high gel strength, characterized in that it comprises the following steps:

[0005] S1. Add agar powder to STPP or SPP aqueous solution and react while stirring. Keep the temperature at 30-60°C and the pH at alkaline during the addition and reaction.

[0006] S2. Filter the reactants, wash them repeatedly with water for several times, dry them, and then crush and sieve them to obtain modified agar with high water retention and high gel strength.

[0007] Further, in step S1, the mass concentration of the STPP aqueous solution is 7%-15%; more preferably, 11%;

[0008] The mass concentration of the SPP aqueous solution is 5%-15%; more preferably, it is 12.5%.

[0009] Furthermore, in step S1, the amount of agar powder added is 3w / v%-9w / v%; more preferably, 7%.

[0010] Further, in step S1, the pH value is 8-12; the method of maintaining the pH at an alkaline state is to add an alkaline reagent;

[0011] When it is an STPP aqueous solution, more preferably, the pH value is 10-11; most preferably, the pH value is 11;

[0012] When it is an SPP aqueous solution, more preferably, the pH value is 10.

[0013] Furthermore, the alkaline reagent is a NaOH solution.

[0014] Furthermore, in step S1, the reaction time is 1-3 h; more preferably, 1.5-2 h; most preferably, 2 h.

[0015] Furthermore, in step S2, the filtering is filtering with filter cloth; and the drying is drying at 40-60° C. for 20-30 hours.

[0016] Furthermore, the drying is performed at 60° C. for 24 hours.

[0017] The invention adopts a chemical modification method, which is simple and easy to operate, does not require a catalyst, requires few reagents, and is safe and non-toxic. The prepared agar has multiple characteristics such as high water retention, high gel strength and high transparency. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 1 is a graph showing the gel strength and dehydration rate of the modified agar gel prepared under different parameter conditions in Example 1.

[0019] Figure 2 1 is a graph showing the viscosity average molecular weight analysis results of the modified agar gel prepared under different temperature conditions in Example 2.

[0020] Figure 3 It is a viscosity-temperature curve detection and analysis diagram of the modified agar gel prepared under different temperature conditions in Example 2.

[0021] Figure 4 This is a graph showing the results of seven freeze-thaw cycles of the modified agar gel prepared under different temperature conditions in Example 2.

[0022] Figure 5 It is the thermogravimetric scanning result figure of the modified agar prepared under different temperature conditions in Example 2.

[0023] Figure 6 This is the infrared scanning result diagram of 30℃-STAG and 60℃-STAG obtained in Example 2.

[0024] Figure 7 This is the microstructure diagram of the 30°C-STAG and 60°C-STAG agar gels prepared in Example 2.

[0025] Figure 8 This is the result of X-ray diffraction analysis of 30°C-STAG and 60°C-STAG prepared in Example 2.

[0026] Fig. 9 This is the result of low-field nuclear magnetic resonance detection of 30°C-STAG and 60°C-STAG gels prepared in Example 2 before and after freeze-thaw.

[0027] Fig.10 This is a graph showing the texture analysis results of the 30°C-STAG and 60°C-STAG gels prepared in Example 2.

[0028] Fig.11 It is a comparison chart of gel strength and dehydration rate between original agar, 30℃-STAG, 60℃-STAG and blank control group.

[0029] Fig.12 It is a comparison chart of the swelling properties of original agar, 30℃-STAG, 60℃-STAG and blank control group.

[0030] Fig.13 This is a graph showing the test results of the effects of different drying processes on STPP modified agar.

[0031] Fig.14 1 is a graph showing the test results of gel strength and dehydration rate of different amounts of STPP and agar mixed in Example 8.

[0032] Fig.15 This is the single factor optimization result diagram of Example 9.

[0033] Fig.16 This is the test result graph of gel strength and dehydration rate of blending group and experimental group with different SPP addition amounts.

[0034] Fig.17 10 is a graph of the viscosity average molecular weight of the modified agar with high water retention and high gel strength prepared at different temperatures.

[0035] Fig.18 It is a viscosity-temperature curve diagram of the modified agar with high water retention and high gel strength prepared at different temperatures in Example 10.

[0036] Fig.19 10 is a Zeta potential diagram of the modified agar with high water retention and high gel strength prepared at different temperatures.

[0037] Fig. 20 These are the infrared spectra of 40°C-SPAG and 60°C-SPAG prepared in Example 10.

[0038] Fig.21 This is a diagram of the mechanism of the modified agar with high water retention and high gel strength prepared in Example 10.

[0039] Fig. 22 This is the powder scanning electron microscope image of 40℃-SPAG and 60℃-SPAG prepared in Example 10.

[0040] Fig.23 This is the gel scanning electron micrograph of 40°C-SPAG and 60°C-SPAG prepared in Example 10.

[0041] Fig.24 These are the low-field nuclear magnetic resonance images of the 40°C-SPAG and 60°C-SPAG gels prepared in Example 10 before and after freeze-thawing.

[0042] Fig.25 It is the texture analysis diagram of 40℃-SPAG and 60℃-SPAG gel prepared in Example 10. DETAILED DESCRIPTION

[0043] Embodiments of the present invention are described in detail below, and the examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals represent the same or similar elements or elements with the same or similar functions from beginning to end. The embodiments described below by reference to the accompanying drawings are exemplary, are intended to be used to explain the present invention, and are not to be construed as limitations of the present invention. Those who do not indicate specific techniques or conditions in the embodiments are carried out according to the techniques or conditions described in the documents in this area or according to the product specification. Those who do not indicate the manufacturer of reagents or instruments used are all conventional products that can be obtained commercially.

[0044] The index testing method used in the following examples is:

[0045] (1) Degree of substitution

[0046] The digestion method of the sample was referred to GB5009.87-201, and the determination method and calculation of the degree of substitution were referred to Zhang Cong, He Huimin, Zhang Yonghui, Xiao Qiong, Xiao Anfeng, Yang Qiuming. Application of phosphate agar in fermented soy milk process [J]. Food Science and Technology, 2019, 44(10): 300305. DOI: 10.13684 / j.cnki.spkj.2019.10.050.

[0047] (2) Determination of gel strength

[0048] Prepare 1.5% (w / v) agar solution and record the weight, heat it to fully dissolve it, add water again to constant weight, pour the solution into a flat dish while it is still hot, cover it with plastic wrap after cooling and solidification, and place it at room temperature for 10-12 hours. Before measuring, place it in a 20℃ incubator to stabilize for 2 hours, and measure its gel strength within 30 seconds using a gel strength meter.

[0049] (3) Determination of dehydration rate

[0050] Prepare a 1.5% (w / v) hot agar solution and keep it constant weight, divide it into three parts by weight, pour it into centrifuge tubes while hot, leave it at room temperature for 12 hours to form a stable gel, record the weight at this time as m1, then freeze it at -18°C for 24 hours, and then transfer the centrifuge tube to room temperature for thawing for 10 hours. After thawing, centrifuge the sample at 3500×g for 20 minutes, pour out the supernatant and weigh the weight at this time, record it as m2. Repeat the freezing cycle up to seven times. The calculation formula for the dehydration rate of the agar sample is as follows:

[0051]

[0052] (4) Sulfate and 3,6-AG

[0053] The determination method of sulfate and 3,6-AG refers to the literature "Xie Shanyu, Wan Bokai, Zhu Yanbing, Jiang Zedong, Xiao Anfeng, Ni Hui, Li Qingbiao, Jiang Qingxiang, Yu Yangjun, Mao Zijian. Establishment and application of Gracilaria agar alkaline extraction process model [J]. Journal of Jimei University (Natural Science Edition), 2022, 27(01): 45-54. DOI: 10.19715 / j.jmuzr.2022.01.05.".

[0054] (5) Transparency

[0055] Prepare 1.5% (w / v) agar solution, dissolve it in microwave until constant weight is reached, pour it into a cuvette while hot, cool it at room temperature, and place it in a 20°C incubator overnight after solidification. Set the transmittance of distilled water to 100% in the spectrophotometer, and measure the transmittance of the sample at a wavelength of 700nm, which is the transparency.

[0056] (6) Viscosity, whiteness and turbidity

[0057] The viscosity was measured by using a DV-C digital viscometer at 80°C for 1.5% (w / v) agar solution. For the whiteness measurement, the agar sample was passed through an 80-mesh sieve and placed in a WSB-2 whiteness meter. For the turbidity, zero turbidity water was used as a blank for zero adjustment, and then 1.5% (w / v) agar solution was placed at 85°C, and the turbidity value was read after the value stabilized.

[0058] (7) Ash content, solidification temperature, melting temperature and dissolution temperature

[0059] The methods for ash content, solidification temperature, melting temperature and dissolution temperature are all based on the reference "Zhang Jiabin. Extraction of Gracilaria agar and preparation process of agar esterified with maleic anhydride and its application [D]. Jimei University, 2019.".

[0060] (8) Determination of swelling properties

[0061] Accurately weigh 0.150 g of agar into a 18*180 mm glass test tube, then transfer 10 mL of distilled water into it. Place the test tube in a constant temperature water bath at 80°C. After 1 hour, take it out and cool it to room temperature. Observe the swelling of different agar samples.

[0062] Example 1: Preparation of modified agar with high water retention and high gel strength

[0063] 1. The preparation process is:

[0064] Weigh a certain volume of distilled water, place it on a magnetic stirrer, set the reaction temperature and speed, add STPP, and prepare a certain concentration of STPP solution. After heating to the reaction temperature, add a certain mass of agar powder to prepare a mixed solution, adjust the pH of the reaction system with NaOH solution, and keep the system pH within a certain range during the reaction. After the reaction reaches the set time, terminate the reaction immediately, filter the filter cloth, and continue to wash the modified agar powder with distilled water several times to remove residual reagents. After drying the washed agar powder at 55°C for 24 hours, crush and sieve to obtain modified agar with high water retention and high gel strength.

[0065] 2. Single factor study on the process of the above preparation method

[0066] (1) Single factor study of STPP addition:

[0067] The original agar was used as the test material, and 5%, 7%, 9%, 11%, 13%, and 15% (w / w) STPP solutions were prepared. The reaction temperature was controlled to be 40°C, and 5% (w / v) agar was added after reaching the reaction temperature. The initial pH value of the reaction was adjusted to 10, and during the reaction, 4% (w / v) NaOH solution was used to maintain the pH of the reaction system between 10 and 10.1. The reaction was terminated immediately after 2 hours of reaction. The solution was filtered, washed, dried, crushed, and sieved to obtain a modified agar with high water retention strength.

[0068] Test the water retention and gel strength of the prepared modified agar with high water retention and high gel strength. The test results are shown in Figure 1 (a).

[0069] Figure 1 The results of (a) show that when the amount of STPP added is 7-15% (w / w), the agar gel strength and dehydration rate reach a good state. When the amount of STPP added is 11% (w / w), the agar gel strength reaches a maximum of 1336.3±27.9g / cm 2 (Original agar is 1147.5±24.3g / cm 2 ), the dehydration rate was 3.4±0.2% (the original agar was 28.1±0.3%).

[0070] (2) Single factor study on agar-to-liquid ratio:

[0071] Prepare 11% (w / w) STPP solution, add agar at a solid-liquid ratio of 3%, 5%, 7%, 9%, 11%, 15% (w / v), control the reaction temperature to 40°C, adjust the initial pH value of the reaction to 10 with 4% (w / v) NaOH solution, and use 4% (w / v) NaOH solution to keep the pH of the reaction system between 10-10.1 during the reaction, and terminate the reaction immediately after 2 hours of reaction. Filter, wash, dry, crush and sieve to obtain the modified product.

[0072] Test the water retention and gel strength of the prepared modified agar with high water retention and high gel strength. The test results are shown in Figure 1 (b).

[0073] Figure 1 The results of (b) show that when the agar addition amount is 3-9% (w / w), the agar gel strength and dehydration rate reach a good state. When the agar addition amount is 7% (w / v), the agar gel strength reaches a maximum of 1384.9±24.0g / cm 2 (Original agar is 1144.8±24.7g / cm 2 ), the dehydration rate was 3.7±0.8% (the original agar was 24.8±1.8%).

[0074] (3) Single factor study of pH of reaction system:

[0075] Prepare 11% (w / w) STPP solution, control the reaction temperature to 40°C, add 7% (w / v) agar, and drop 1 mol / L HCl solution or 4% (w / v) NaOH solution during the reaction to adjust the system pH to 7-7.1, 8-8.1, 9-9.1, 10-10.1, 11-11.1, 12-12.1, 13-13.1, respectively, and terminate the reaction immediately after 2 hours of reaction. Filter, wash, dry, crush and sieve to obtain the modified product.

[0076] Test the water retention and gel strength of the prepared modified agar with high water retention and high gel strength. The test results are shown in Figure 1 (c).

[0077] Figure 1 (c) The results show that when the pH of the reaction system is 10-11, the agar gel strength and dehydration rate reach a good state. When the pH of the reaction system is 11, the agar gel strength reaches a maximum of 1431±37.7g / cm 2 (Original agar is 1154.2±19.1g / cm 2 ), the dehydration rate was 6.2±0.8% (the original agar was 25.1±2.8%).

[0078] (4) Single factor study of reaction time:

[0079] Prepare 11% (w / w) STPP solution, control the reaction temperature to 40°C, add 7% (w / v) agar, and use 4% (w / v) NaOH solution to adjust the system pH to 11-11.1 during the reaction. Control the reaction time to 0.5h, 1h, 1.5h, 2h, 3h, 4h, 5h respectively, and terminate the reaction when the reaction reaches the specified time. Filter, wash, dry, crush and sieve to obtain the modified product.

[0080] Test the water retention and gel strength of the prepared modified agar with high water retention and high gel strength. The test results are shown in Figure 1 (d).

[0081] Figure 1 The results of (d) show that when the reaction time is 1-3h, more preferably 1.5-2h, the agar gel strength and dehydration rate reach a better state. When the reaction time is 2h, the agar gel strength reaches a maximum of 1419.5±17.3g / cm 2 (Original agar is 1169.3±14.2g / cm 2 ), the dehydration rate was 5.5±1.3% (the original agar was 27.8±0.2%).

[0082] (5) Single factor study of reaction temperature:

[0083] Prepare 11% (w / w) STPP solution, add 7% (w / v) agar, adjust the system pH to 11-11.1 with 4% (w / v) NaOH solution, and control the reaction temperature to 20°C, 30°C, 40°C, 50°C, and 60°C respectively. Terminate the reaction immediately after 2 hours of reaction. Filter, wash, dry, crush and sieve to obtain the modified product.

[0084] Test the water retention and gel strength of the prepared modified agar with high water retention and high gel strength. The test results are shown in Figure 1 (e).

[0085] Figure 1 The results of (e) show that when the reaction time is 40-60℃, the agar gel strength and dehydration rate reach a good state. When the reaction temperature is 60℃, the agar gel strength reaches a maximum of 1529.4±11.4g / cm 2 (Original agar 1165.8±10.3g / cm 2 ), the dehydration rate was 9.0±2.9% (the original agar was 26.3±0.8%).

[0086] Example 2: Preparation of modified agar with high water retention and high gel strength

[0087] (1) Prepare 300 mL of 11% (w / w) STPP solution with water;

[0088] (2) 300 mL of STPP solution was placed on a magnetic stirrer and stirred, and 21 g of agar powder was added and reacted for 2 h; during the entire reaction period, the reaction temperature was maintained at 20° C., 30° C., 40° C., 50° C., and 60° C., and the reaction system pH was maintained at 11;

[0089] (3) After the reaction is completed, the mixture is washed with water three times, filtered, dehydrated and dried to obtain a modified agar with high water retention and high gel strength.

[0090] Table 1 Comparison of the physical and chemical properties of original agar and modified agar prepared at different temperatures

[0091]

[0092]

[0093] Note: The data after “±” are standard deviations (n=3). Different letters in the same row in the table represent significant differences (P<0.05).

[0094] Table 1 shows that the gel strength of modified agar increased significantly with increasing temperature (P<0.05) and reached a maximum value (1529.4 g / cm2 ), compared with the original agar (1165.8g / cm 2 ) increased by about 31.2%. Similarly, with the increase of temperature, the sulfate content continued to decrease and reached a minimum value (0.95%) at 60°C, which was about 45.7% lower than that of the original agar (2.08%). The transparency also increased with the increase of temperature and was higher than that of the original agar (60.5%). This is because after the phosphate group was connected to the side chain of agar, the chain length increased. In the process of gel formation, the intermolecular association was hindered, and the light was easier to transmit.

[0095] Example 3 Performance Characterization and Structural Analysis of Modified Agar with High Water Retention and High Gel Strength

[0096] (1) Characterization of modified agar with high water retention and high gel strength - viscosity average molecular weight analysis

[0097] The viscosity average molecular weight analysis of the modified agar gel prepared under different temperature conditions in Example 2 is shown in FIG. Figure 2 .

[0098] Figure 2 The results showed that for modified agar, as the reaction temperature increased, the molecular weight of STAG gradually increased. When the reaction temperature reached 60°C, the molecular weight of modified agar was 5.5×10 5 g / mol, much larger than the original agar (4.1×10 5 g / mol), which is attributed to the formation of cross-linked diester agar at high temperature, which has the ability to form a three-dimensional network structure under aqueous conditions.

[0099] (2) Characterization of modified agar with high water retention and high gel strength - viscosity-temperature curve detection

[0100] The viscosity-temperature curve of the modified agar gel prepared under different temperature conditions in Example 2 was tested. The results are shown in Figure 3 .

[0101] Figure 3 The results show that at the same temperature, the viscosity of the modified agar is higher than that of the original agar, and increases with the increase of reaction temperature, which may be due to the increased entanglement caused by the side chain phosphate groups, which hinders the flow of the gel. However, the viscosity of 60℃-STAG decreases, which may be due to the reduction of the side chain phosphate groups of the cross-linked diester and the degradation under high temperature. The viscosity slope of 60℃-STAG rises fastest in the range of 45℃ to 40℃, which is related to its high gel strength.

[0102] (3) Characterization of modified agar with high water retention and high gel strength - freeze-thaw stability analysis

[0103] The modified agar gel prepared under different temperature conditions in Example 2 was subjected to seven freeze-thaw cycles. Figure 4 .

[0104] Figure 4 (Note: FT cycle-1 means 1 freeze-thaw cycle, FT cycle-2 means 2 freeze-thaw cycles, and so on. The significant differences between different samples of the same freeze-thaw cycle are indicated by lowercase letters, and the significant differences between the same sample after different freeze-thaw cycles are indicated by uppercase letters.) The results show that the network structure of agar gel is easily destroyed by ice crystals, resulting in water separation during thawing. After 1-7 freeze-thaw cycles, the dehydration rate of the original agar gel increased from 26.3±0.8% to 41.5±2.1%, and the dehydration rate of the original agar was the highest in each cycle of the sample. The dehydration rate of agar gel was significantly reduced by STPP esterification modification. The dehydration rate of the modified sample at 30°C increased from 1.9±0.6% to 6.1±0.2% after 7 freeze-thaw cycles.

[0105] (4) Characterization of STPP modified agar performance - thermogravimetric scanning

[0106] The modified agar prepared at different temperatures in Example 2 was subjected to thermogravimetric scanning, and the results are shown in Figure 5 .

[0107] Figure 5 The results showed that the thermogravimetric graph was divided into two stages. The first stage was between 30℃ and 180℃, and the pilot test of the original agar and phosphorylated agar was around 11.1%-12.7%. The reduction in mass in this stage was mainly related to the evaporation of bound water and free water in the agar samples. The water holding capacity of agar can be expressed by the water loss rate. It was observed that the water loss rate of the modified agar was significantly lower than that of the original agar, and the water loss rate of 30℃-STAG agar was the lowest, indicating that 30℃-STAG had the highest water holding capacity. This was because phosphorylated agar introduced hydrophilic groups and enhanced its water adsorption capacity, which was consistent with the previous freeze-thaw stability results. The second stage was between 200℃ and 400℃, and all agar samples showed an obvious mass loss, which represented the thermal decomposition of agar. As the temperature increased to 600℃, the sample continued to slowly lose weight to about 25% of the original, which was consistent with the ash results.

[0108] (5) Characterization of modified agar with high water retention and high gel strength - Fourier transform infrared spectroscopy analysis

[0109] The modified agar at 30°C and 60°C obtained in Example 2 was scanned by infrared using potassium bromide tabletting method. Figure 6 .

[0110] Figure 6The results showed that in the infrared absorption spectrum of STPP modified agar, not only the infrared absorption characteristic peak of the original agar was retained, but also the infrared absorption characteristic peak of the modified agar at 3420cm -1 The peak width at 30℃-STAG becomes wider, which is attributed to the possible connection between the phosphate group and the -OH group. -1 A new absorption peak appears at 1280 cm-1, which belongs to the stretching vibration peak of P=O. Interestingly, 60℃-STAG has a peak at 1280 cm-1. -1 The absorption peak at 986 cm -1 A new absorption peak appears at , which is the stretching vibration peak of the POC bond, indicating that at high temperature, the phosphate group and agar mainly undergo esterification cross-linking.

[0111] (6) Characterization of modified agar gel with high water retention and high gel strength - Field emission scanning electron microscopy

[0112] The microstructure of the 30°C and 60°C modified agar gels prepared in Example 2 was observed by field emission scanning electron microscopy. Figure 7 . (A: original agar, B: 30℃ modified agar, C: 60℃ modified agar) (Magnification: 1: 5.0k, 2: 10.0k, 3: 30.0k. That is, A1 is the original agar magnified at 5.0k; A2 is the original agar magnified at 10.0k...C2 is the 60℃ modified agar magnified at 10.0k; C3 is the 60℃ modified agar magnified at 30.0k)

[0113] Figure 7 The results showed that the original agar exhibited the finest gel network with larger pores. The network structure of the esterified agar exhibited a "membrane-like" structure, which has a larger contact area with water and is conducive to locking water firmly, which is attributed to the participation of phosphates attached to the agar in network formation, which is consistent with the high water retention of the esterified agar. For the cross-linked agar, a more ordered, denser, and thicker chain structure was observed, which is conducive to the temperature of the structure, resulting in an increase in gel strength, and a decrease in "membrane-like" structure and a decrease in water retention.

[0114] (7) Characterization of modified agar with high water retention and high gel strength - X-ray photoelectron spectroscopy analysis

[0115] The modified agar powders at 30°C and 60°C prepared in Example 2 were analyzed by X-ray photoelectron spectroscopy. Figure 8 .

[0116] Figure 8 The results showed that only C1s and O1s peaks were clearly observed in the XPS spectra of the original agar and the modified agar, while P2p and N1s were not clearly observed. Figure 8(b) and (c) are the C1s spectra of the original agar and the modified agar. It was observed that they all have three common characteristic peaks, namely 284.9eV (CC), 286.5eV (CO) and 287.9eV (C=O). Due to the introduction of the phosphate group, the modified agar has a new characteristic peak COP bond at 289.4eV, which is consistent with the results of FT-IR. In addition, Figure 8 (e) shows that the modified agar also has a new peak P=O bond at 534.5 eV, which is not observed in the spectrum of the original agar. These results confirm that STPP successfully modifies agar.

[0117] (8) Characterization of modified agar with high water retention and high gel strength - low-field nuclear magnetic resonance analysis

[0118] The modified agar gel prepared under different temperature conditions before and after freezing and thawing in Example 2 was subjected to low-field nuclear magnetic resonance detection. The results are shown in Fig. 9 .

[0119] Fig. 9 The results show that before freezing and thawing, the T2 relaxation time of agar gel has only two peaks, which represent the different states of water in the gel. 21 ) and the second peak (T 22 ) represents the water retained by the gel network structure, i.e., water that is not easy to flow. After one freeze-thaw, the original agar and modified agar gels both showed a third peak (T 23 ), which represents water that can migrate freely, i.e., free water. This indicates that freeze-thaw cycles can transform the immobile water in agar gel into free water, increase the fluidity of water, and reduce the water holding capacity. This also explains the reason for water loss after freeze-thaw. The third peak of modified agar (T 23 ) has only a lower signal intensity than the original agar, which is because the content of the non-mobile water converted into free water is less, and it has better freeze-thaw stability. Interestingly, the second peak (T 22 ) and the third peak (T 23 ) changes are not consistent, the third peak of the original agar (T 23 ) is the second peak (T 22 ) shoulder peak, these two peaks represent the water state between fixed water and free water, the second peak of the modified agar sample (T 22 ) increases, because the mobility of bound water is slightly improved, but there is no tendency to transform into free water.

[0120] (9) Characterization of modified agar with high water retention and high gel strength - texture analysis

[0121] The texture analysis of the modified agar gel prepared under different temperature conditions in Example 2 was performed, and the results are shown in Fig.10 .

[0122] Fig.10 The results showed that compared with the original agar, the modified agar showed great differences in hardness, chewiness, viscosity and cohesion. The hardness of NA, 30℃-STAG and 60℃-STAG were 15.6N, 17.3N and 18.4N, respectively. The hardness was consistent with the gel strength trend of agar. The higher the gel strength, the higher the chewiness in food applications. The chewiness of 30℃-STAG and 60℃-STAG were 5.7N and 5.9N, respectively, which were higher than that of NA (4.0N).

[0123] Example 4: Performance comparison at different reaction temperatures

[0124] According to the preparation method of the modified agar with high water retention and high gel strength prepared in Example 2, a blank control group was prepared, comprising the following steps:

[0125] 300 mL of water was stirred on a magnetic stirrer, and 21 g of agar powder was added to react for 2 h; during the entire reaction period, the reaction temperature was maintained at 30 ° C and 60 ° C, and the reaction system pH was maintained at 11. After the reaction was completed, the sample was repeatedly washed with water for 3 times, filtered, dehydrated, and dried to obtain a blank control group sample.

[0126] The gel strength and dehydration rate of the original agar, the modified agar at 30℃, 60℃ and the blank control group are shown in Fig.11 shown.

[0127] Fig.11 The results showed that the gel strength and dehydration rate of the blank control group at 30℃ and 60℃ did not change significantly compared with the experimental group. This is because the properties of agar such as gel strength and dehydration rate cannot be changed by simply changing the pH and reaction temperature. This indicates that the improvement in water retention and gel strength of the modified agar is due to the successful esterification of agar by STPP.

[0128] The swelling properties of the original agar, the modified agar at 30℃, 60℃ and the blank control group are shown in Fig.12 shown.

[0129] Fig.12The results showed that the swelling of the blank control group at 30℃ and 60℃ did not significantly expand compared with the original agar, while the swelling volume of 30℃-STAG and 60℃-STAG modified agar increased significantly compared with the original agar. This was due to the phosphate groups introduced after STPP modification. The phosphate groups not only increased its hydrophilicity and accelerated its diffusion rate in water, but also caused electrostatic repulsion and increased the intermolecular chain distance, which further improved the diffusion of agar molecules in water and the degree of swelling. In addition, they can also form hydrogen bridges, allowing more water molecules to be received, thereby ensuring that the water that penetrates the particles is retained to a higher degree. Therefore, at the same high temperature, STPP modified agar is easier to swell than original agar, is sensitive to heat, and is easier to dissolve.

[0130] Example 5: Test on the effect of washing process on STPP modified agar

[0131] According to the preparation method of the modified agar with high water retention and high gel strength prepared in Example 2, the modified agar was esterified at 30°C and 60°C, and a certain amount of agar was directly taken out after the reaction was completed, and its gel strength and dehydration rate were measured. The remaining agar was continued to be washed, and the same amount of agar was taken out again after washing, and its gel strength and dehydration rate were measured.

[0132] The results of gel strength and dehydration rate are shown in Table 3. The results in Table 3 show that whether the STPP modified agar is washed or not has the same trend on gel strength and dehydration rate at different temperatures: the gel strength of the "washed" group is higher than that of the "unwashed" group. This may be due to the influence of residual STPP in the unwashed solution. The presence of sodium ions will weaken the interaction between the agar molecular chains. When the gel is formed, the degree of entanglement of the molecular chains is reduced, and the number of network nodes formed is reduced, resulting in a decrease in gel strength; the dehydration rate of the "unwashed" group is higher than that of the "washed" group. This may be because after the gel is centrifuged, water is more easily combined with phosphate and lost, resulting in an increase in the dehydration rate.

[0133] Table 2 Gel strength and dehydration rate of modified agar in different washing processes

[0134]

[0135] Example 6: Experiment on the effect of drying process on STPP modified agar

[0136] According to the preparation method of the modified agar with high water retention and high gel strength prepared in Example 2, the modified agar was esterified at 30°C and 60°C, and a portion of the agar was directly taken after filtering and washing after the reaction was completed to detect the gel strength and dehydration rate of the "undried" group, and the remaining modified agar was dried and crushed to obtain the modified agar, and the gel strength and dehydration rate of the "dried" group were detected.

[0137] The results of the gel strength and dehydration rate are shown in Table 2. The results in Table 2 show that there is no difference in the gel strength and water retention of STPP modified agar prepared at different temperatures, which also indicates that the esterification reaction of STPP has been completed before drying, and there is no further esterification reaction during the drying process.

[0138] Table 3 Gel strength and dehydration rate of modified agar in different drying processes

[0139]

[0140] Example 7: Experiment on the influence of different drying processes on STPP modified agar

[0141] According to the preparation method of the modified agar with high water retention and high gel strength prepared in Example 2, after the reaction is completed, filtered and washed, a portion is freeze-dried and crushed to obtain a modified sample, and the remaining portion is dried to test the gel strength and dehydration rate of the agar under different drying methods. The results are as follows: Fig.13 .

[0142] Fig.13 The results showed that the trends of the modified agar drying methods at 30℃ and 60℃ were consistent. This was because the drying process caused the agar to decompose due to the higher temperature compared to the freeze-drying process, resulting in shorter chain lengths, fewer double-chain entanglements, and fewer bound network nodes, leading to lower gel strength. However, the hydrophilic groups became more easily exposed and had a stronger ability to bind water, resulting in a lower dehydration rate.

[0143] Example 8: Gel strength and dehydration rate test of different amounts of STPP and agar

[0144] A 1.5% (w / v) agar solution was prepared, and 0.15 g, 0.3 g, 0.5 g, 0.7 g and 1 g of STPP were added, respectively, and then dissolved by microwave. After standing at room temperature overnight, the gel strength and dehydration rate of the gel were measured. The gel strength and dehydration rate of agar and different amounts of STPP were blended as shown in Figure 2. Fig.14 shown.

[0145] Fig.14 The results showed that when the amount of STPP added was less than 0.5 g, the gel strength did not change significantly, but when 1.0 g STPP was added, the gel strength reached 1256 g / cm 2 , compared with the original agar (1174.8g / cm 2 ) did not increase significantly, which may be because excessive STPP affects the pH of the system, thereby affecting the gel properties of agar. The dehydration rate increases with the increase in the amount of STPP added because the attraction of residual STPP to water is greater than that of agar to water. After frozen centrifugation, water is lost with the residual phosphate, which also indicates that STPP successfully esterifies agar.

[0146] In the present invention, 1.5% (w / v) means that 100 ml of water contains 1.5 g of agar (solute), and 1% (w / w) means that when the mass of agar is 100 g, the amount of STPP added is 1 g. Agar and sodium hydroxide solution are calculated in (w / v).

[0147] Example 9: Preparation of modified agar with high water retention and high gel strength

[0148] 1. The preparation process is:

[0149] Weigh a certain volume of distilled water, place it on a magnetic stirrer, set the reaction temperature and speed, prepare a certain concentration of sodium pyrophosphate (SPP) solution, heat it to the reaction temperature, add a certain mass of agar powder to prepare a mixed solution, adjust the pH of the reaction system with NaOH solution, and keep the system pH within a certain range during the reaction. After the reaction reaches the set time, terminate the reaction immediately, filter the filter cloth, and continue to wash the modified agar powder with distilled water 4 times to remove residual reagents. After drying the washed agar powder at 55°C for 24 hours, crush it through an 80-mesh sieve, store the modified product in a ziplock bag, and keep it dry for use. Three parallel groups are performed for each group of experiments.

[0150] 2. Single factor study on the process of the above preparation method

[0151] (1) Single factor study of SPP addition:

[0152] Use the original agar as the test material, prepare 5%, 7.5%, 10%, 12.5%, 15% (w / w) STPP solution, control the reaction temperature to 40°C, add 7% (w / v) agar after reaching the reaction temperature, adjust the initial pH value of the reaction to 10, and use 4% (w / v) NaOH solution to keep the pH of the reaction system between 10-10.1 during the reaction. Terminate the reaction immediately after 2 hours of reaction. Filter, wash, dry, crush and sieve to obtain the modified product. Test the water retention and gel strength of the prepared modified agar with high water retention and high gel strength. See the test results. Fig.15 (a).

[0153] Fig.15 The results of (a) show that when the SPP addition amount is 7-15% (w / w), the agar gel strength and dehydration rate reach a good state. When the SPP addition amount is 11% (w / w), the agar gel strength reaches a maximum of 1336.3±27.9g / cm 2 (Original agar is 1147.5±24.3g / cm 2 ), the dehydration rate was 3.4±0.2% (the original agar was 28.1±0.3%).

[0154] (2) Single factor study on agar-to-liquid ratio:

[0155] Prepare 10% (w / w) SPP solution, add agar at a solid-liquid ratio of 1%, 3%, 5%, 7%, and 9% (w / v), control the reaction temperature to 40°C, use 4% (w / v) NaOH solution to adjust the initial pH value of the reaction to 10, and use 4% (w / v) NaOH solution during the reaction to keep the pH of the reaction system between 10-10.1, and terminate the reaction immediately after 2 hours of reaction. Filter, wash, dry, crush and sieve to obtain the modified product. Test the water retention and gel strength of the prepared high water retention and high gel strength modified agar. The test results are shown in Figure 1 (b).

[0156] Fig.15 The results of (b) show that when the agar addition amount is 3-9% (w / w), the agar gel strength and dehydration rate reach a good state. When the agar addition amount is 7% (w / v), the agar gel strength reaches a maximum of 1384.9±24.0g / cm 2 (Original agar is 1144.8±24.7g / cm 2 ), the dehydration rate was 3.7±0.8% (the original agar was 24.8±1.8%).

[0157] (3) Single factor study of pH of reaction system:

[0158] Prepare 10% (w / w) SPP solution, control the reaction temperature to 40°C, add 7% (w / v) agar, and add 1 mol / L HCl solution or 4% (w / v) NaOH solution during the reaction to adjust the system pH to 8-8.1, 9-9.1, 10-10.1, 11-11.1, 12-12.1, respectively, and terminate the reaction immediately after 2 hours of reaction. Filter, wash, dry, crush and sieve to obtain the modified product.

[0159] Test the water retention and gel strength of the prepared modified agar with high water retention and high gel strength. The test results are shown in Figure 1 (c).

[0160] Fig.15 (c) The results show that when the pH of the reaction system is 10-11, the agar gel strength and dehydration rate reach a good state. When the pH of the reaction system is 11, the agar gel strength reaches a maximum of 1431±37.7g / cm 2 (Original agar is 1154.2±19.1g / cm 2 ), the dehydration rate was 6.2±0.8% (the original agar was 25.1±2.8%).

[0161] (4) Single factor study of reaction time:

[0162] Prepare 10% (w / w) SPP solution, control the reaction temperature to 40°C, add 7% (w / v) agar, and adjust the system pH to 11-11.1 during the reaction. Control the reaction time to 0.5h, 1h, 1.5h, 2h, and 3h respectively, and terminate the reaction when the reaction reaches the specified time. Filter, wash, dry, crush and sieve to obtain the modified product.

[0163] Test the water retention and gel strength of the prepared modified agar with high water retention and high gel strength. The test results are shown in Figure 1 (d).

[0164] Fig.15 The results of (d) show that when the reaction time is 1-3h, more preferably 1.5-2h, the agar gel strength and dehydration rate reach a better state. When the reaction time is 2h, the agar gel strength reaches a maximum of 1419.5±17.3g / cm 2 (Original agar is 1169.3±14.2g / cm 2 ), the dehydration rate was 5.5±1.3% (the original agar was 27.8±0.2%).

[0165] (5) Single factor study of reaction temperature:

[0166] Prepare 10% (w / w) SPP solution, control the reaction temperature to 40°C, add 7% (w / v) agar, adjust the system pH to 11-11.1, and control the reaction temperature to 20°C, 30°C, 40°C, 50°C, and 60°C respectively. Terminate the reaction immediately after 2 hours of reaction. Filter, wash, dry, crush and sieve to obtain the modified product. Test the water retention and gel strength of the prepared high water retention and high gel strength modified agar. See the test results. Fig.15 (e).

[0167] Fig.15 The results of (e) show that when the reaction time is 40-60℃, the agar gel strength and dehydration rate reach a good state. When the reaction temperature is 60℃, the agar gel strength reaches a maximum of 1529.4±11.4g / cm 2 (Original agar 1165.8±10.3g / cm 2 ), the dehydration rate was 9.0±2.9% (the original agar was 26.3±0.8%).

[0168] Example 10: Preparation of modified agar with high water retention and high gel strength

[0169] (1) Prepare 300 mL of 10% (w / w) SPP solution with water;

[0170] (2) 300 mL of SPP solution was placed on a magnetic stirrer and stirred, and 21 g of agar powder was added and reacted for 2 h; during the entire reaction period, the reaction temperature was maintained at 20° C., 30° C., 40° C., 50° C., and 60° C., and the reaction system pH was maintained at 11;

[0171] (3) After the reaction is completed, the mixture is washed with water three times, filtered, dehydrated and dried to obtain a modified agar with high water retention and high gel strength.

[0172] Table 4 Comparison of the physical and chemical properties of original agar and modified agar prepared at different temperatures

[0173]

[0174]

[0175] Note: The data after “±” are standard deviations (n=3). Different letters in the same row in the table represent significant differences (P<0.05).

[0176] Table 4 shows that the gel strength of modified agar increased significantly with increasing temperature (P<0.05) and reached a maximum value (1529.4 g / cm 2 ), compared with the original agar (1165.8g / cm 2 ) increased by about 31.2%. Similarly, with the increase of temperature, the sulfate content continued to decrease and reached a minimum value (0.95%) at 60°C, which was about 45.7% lower than that of the original agar (2.08%). The transparency also increased with the increase of temperature and was higher than that of the original agar (60.5%). This is because after the phosphate group was connected to the side chain of agar, the chain length increased. In the process of gel formation, the intermolecular association was hindered, and the light was easier to transmit.

[0177] Example 11 Performance Characterization and Structural Analysis of Modified Agar with High Water Retention and High Gel Strength

[0178] (1) Characterization of modified agar with high water retention and high gel strength - viscosity average molecular weight analysis

[0179] The viscosity average molecular weight analysis of the modified agar gel prepared under different temperature conditions in Example 10 is shown in FIG. Fig.17 .

[0180] Fig.17 The results showed that for the modified agar, as the reaction temperature increased, the molecular weight of SPAG gradually increased. When the reaction temperature reached 60℃, the molecular weight of the modified agar was 5.4×10 5 g / mol, much larger than the original agar (4.0×10 5g / mol), which is attributed to the formation of cross-linked diester agar at high temperature, which has the ability to form a three-dimensional network structure under aqueous conditions.

[0181] (2) Characterization of modified agar with high water retention and high gel strength - viscosity-temperature curve detection

[0182] The viscosity-temperature curve of the modified agar gel prepared under different temperature conditions in Example 10 was tested. The results are shown in Fig.18 .

[0183] Fig.18 The results show that at the same temperature, the viscosity of the modified agar is higher than that of the original agar, and increases with the increase of reaction temperature, which may be due to the increased entanglement caused by the side chain phosphate groups, which hinders the flow of the gel. However, the viscosity of 60℃-SPAG decreases, which may be due to the reduction of the side chain phosphate groups of the cross-linked diester and the degradation under high temperature. The viscosity slope of 60℃-SPAG rises fastest in the range of 45℃ to 40℃, which is related to its high gel strength.

[0184] (3) Characterization of the performance of SPP modified agar - Zeta potential

[0185] The Zeta potential of the modified agar prepared at different temperatures in Example 10 was measured. The results are shown in Fig.19 .

[0186] Fig.19 The results showed that compared with the original agar, the absolute values ​​of the zeta potential of all modified agar samples increased, and showed a trend of first increasing and then decreasing with the increase of reaction temperature. In the range of 20-50℃, the absolute value of the zeta potential of the modified agar samples continued to increase with the increase of reaction temperature, which was attributed to the connection of more and more phosphate groups to agar molecules during the phosphorylation modification process, resulting in more net negative charges on the agar surface. At 60℃, the absolute value of the zeta potential of the modified agar decreased, because cross-linking resulted in the reduction of some phosphate groups.

[0187] (4) Characterization of modified agar with high water retention and high gel strength - Fourier transform infrared spectroscopy analysis

[0188] The modified agar at 40°C and 60°C obtained in Example 2 was subjected to infrared scanning using the potassium bromide tabletting method. Fig. 20 .

[0189] Fig. 20 The results showed that in the infrared absorption spectrum of SPP modified agar, not only the infrared absorption characteristic peak of the original agar was retained, but also the 40℃-SPAG at the wave number 1285cm -1 A new absorption peak appeared at 986 cm-1, which belongs to the stretching vibration peak of P=O.-1 A new peak also appeared at 60℃, which was the stretching vibration peak of the POC bond. This was due to the condensation of the free hydroxyl groups of SPP and agar. The absorption peak of the POC bond of 60℃-SPAG was strengthened and the absorption peak of the P=O bond was weakened. This was attributed to the removal of some phosphate groups while the cross-linking of phosphate monoester agar and agar. In general, SPP was able to successfully modify agar.

[0190] (5) Speculation on the mechanism of modified agar with high water retention and high gel strength

[0191] The mechanism of modified agar was inferred based on the results of Fourier transform infrared spectroscopy analysis. Fig.21 .

[0192] The results showed that there were two main modification modes in the process of SPP modification of agar: esterification and cross-linking. First, (a) sodium hydroxide converted the hydroxyl groups of agar into alcohols, and (b) SPP replaced the formed alcohols to produce monoagardiphosphate (MADP), which is the intermediate product of the cross-linking reaction. In the last step (c), MADP either reacted with NaOH to produce monoagar monophosphate (MAMP), with inorganic phosphate (P) as the byproduct, or reacted with alcohols to produce cross-linked diagar monophosphate (DAMP), with inorganic phosphate (P) as the byproduct.

[0193] (6) Structural characterization of modified agar with high water retention and high gel strength - scanning electron microscopy

[0194] The microstructure of the modified agar gel at 40°C and 60°C prepared in Example 10 was observed by field emission scanning electron microscopy. Fig. 22 (A: original agar, B: 40℃-SPAG, C: 60℃-SPAG) (Magnification: 1000×)

[0195] The results showed that the main morphology of agar powder did not change before and after modification, and both were granular, while 40℃-SPAG and 60℃-SPAG had a wrinkled skeleton structure with fine cracks on the surface. On the one hand, it may be due to the influence of the heterogeneous wet modification process on the particle surface, and on the other hand, it may be due to the introduction of phosphate groups after modification, which leads to enhanced charge repulsion and difficulty in aggregation.

[0196] (7) Characterization of modified agar gel with high water retention and high gel strength - Field emission scanning electron microscopy

[0197] The microstructure of the modified agar gel at 40°C and 60°C prepared in Example 10 was observed by field emission scanning electron microscopy. Fig.23. (A1-A3: original agar, B1-B3: 40℃-SPAG, C1-C3: 60℃-SPAG) (Magnification: 1: 5.0k, 2: 10.0k, 3: 30.0k)

[0198] Fig.23 The results showed that all agar gels showed an interconnected network of fairly uniform chains, however, significant differences were observed between the microstructures of the original agar gel, 40℃-SPAG gel, and 60℃-SPAG gel. The natural agar gel showed the finest gel network with larger pores. The esterified agar (40℃-SPAG) gel network structure showed a "film-like" structure, which resulted in an increase in the interface area and the number of sites provided for binding water, thus improving the water adsorption capacity and making it difficult for water to be lost. For the cross-linked agar (60℃-SPAG), a more ordered, denser, and thicker chain gel network structure was observed, and the thicker "bundles" were conducive to the stability of the network structure and had higher gel strength.

[0199] (8) Characterization of modified agar with high water retention and high gel strength - low-field nuclear magnetic resonance analysis

[0200] The 40°C and 60°C modified agar prepared in Example 10 were subjected to low-field nuclear magnetic resonance detection before and after freeze-thaw, and the results are shown in Fig.24 .

[0201] Fig.24 The results showed that after a freeze-thaw process, the bound water content of the original agar gel (P 22 ) from 99.00% to 45.62% ( Fig.24 B), while the free water content (P 23 ) is as high as 51.89%, which is because freezing and thawing causes a large amount of bound water to transform into free water, indicating that the original agar gel has poor freeze-thaw stability. The third peak (T 23 ) has only a lower signal intensity than the original agar, and the free water content P 23 Only 0.32% and 1.92%, which indicates that the content of free water converted from immobile water is less. This is because after agar is connected to the phosphate group, the binding sites of water molecules increase, which has better freeze-thaw stability. In addition, the free water content of 60℃-SPAG 1 after freeze-thaw is slightly higher than that of 60℃-SPAG 1, which is consistent with the previous research conclusions.

[0202] (9) Characterization of modified agar with high water retention and high gel strength - texture analysis

[0203] The texture analysis of the 40°C and 60°C modified agar gel prepared in Example 2 was performed. Fig.25 .

[0204] Fig.25 The results showed that the original agar and modified agar showed great differences in hardness, chewiness, viscosity and cohesion. The hardness of the original agar, 40℃-SPAG and 60℃-SPAG were 14.0N, 14.6N and 17.4N respectively. In addition, the higher the gel strength, the more energy is required to chew the gel, so the chewiness is also higher. The chewiness of 40℃-SPAG and 60℃-SPAG are 5.3N and 6.0N respectively, which are higher than the chewiness of the original agar (4.4N).

[0205] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A method for preparing agar with high water retention and high gel strength, characterized in that: The steps include: S1. Add agar powder to STPP sodium tripolyphosphate or SPP sodium pyrophosphate aqueous solution and react while stirring. Keep the temperature at 30-60°C and the pH at alkaline during the addition and reaction. S2. The reaction product is filtered, washed repeatedly with water several times, dried, crushed and sieved to obtain a modified agar with high water retention and high gel strength; In step S1, the mass concentration of the STPP aqueous solution is 7%-15%, and the mass concentration of the SPP aqueous solution is 5%-15%; In step S1, the pH value is 8-12; the method of maintaining the pH at an alkaline level is to add an alkaline reagent; In step S1, the added amount of agar powder is 3 w / v%-9 w / v%.

2. The method for preparing agar with high water retention and high gel strength as claimed in claim 1, characterized in that: The mass concentration of the STPP aqueous solution is 11%; the mass concentration of the SPP aqueous solution is 12.5%.

3. The preparation method of agar with high water retention and high gel strength as claimed in claim 1, characterized in that, In step S1, the added amount of agar powder is 7 w / v %.

4. The preparation method of agar with high water retention and high gel strength as claimed in claim 1, characterized in that, When it is an STPP aqueous solution, the pH value is 10-11.

5. The preparation method of agar with high water retention and high gel strength as claimed in claim 4, characterized in that, When it is an STPP aqueous solution, the pH value is 11.

6. The method for preparing agar with high water retention and high gel strength as claimed in claim 1, characterized in that: When it is an SPP aqueous solution, the pH value is 10.

7. The method for preparing agar with high water retention and high gel strength as claimed in claim 1, characterized in that: The alkaline reagent is NaOH solution.

8. The method for preparing agar with high water retention and high gel strength as claimed in claim 1, characterized in that: In step S1, the reaction time is 1-3 h.

9. The method for preparing agar with high water retention and high gel strength as claimed in claim 8, characterized in that: In step S1, the reaction time is 1.5-2 h.

10. The method for preparing agar with high water retention and high gel strength as claimed in claim 9, characterized in that: In step S1, the reaction time is 2 h.

11. The method for preparing agar with high water retention and high gel strength as claimed in claim 1, characterized in that: In step S2, The filtration is performed by filtering with filter cloth; and the drying is performed at 40-60° C. for 20-30 hours.

12. The method for preparing agar with high water retention and high gel strength as claimed in claim 11, characterized in that: The drying step is drying at 60° C. for 24 hours.